Rural Marketing in India: Challenges And Opportunities (International Journal of Engineering and Computer Science, 2014)
In the recent years rural market have acquired significance and attract the attention of marketers as 68.84% population of India reside in 6, 38,000 villages and overall growth of economy has resulted into substantial increase in the purchasing power of the rural communities. Due to green revolution, the rural areas are consuming a large quantity of industrial and manufactured products. In this way rural market offers opportunities in the form of large untapped market, increase in disposable income, increase in literacy level and large scope for penetration. To take the advantage of these opportunities, a special marketing strategy ‘Rural Marketing’ has emerged. This paper tries to understand the rural market, importance of rural marketing and status of rural market. The main aim of the study to observe the potentiality of Indian rural markets and find out various problems are being faced by rural marketer.